2011
DOI: 10.1039/c0cp01387k
|View full text |Cite
|
Sign up to set email alerts
|

Chiral interactions of histidine in a hydrated vermiculite clay

Abstract: Graphical Contents EntryWe report chiral differences in the effects of D-and L-histidine on the interlayer spacing of vermiculite clays that are relevant in assessing the role of clays in the origin of bio-homochirality. AbstractRecent work suggests a link between chiral asymmetry in the amino acid iso-valine extracted from the Murchison meteorite and the extent of hydrous alteration. We present the results of neutron scattering experiments on an exchanged, 1-dimensionally ordered n-propyl ammonium vermiculite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Other peak types are basically a combination of peak shapes of MMT and LDHs. It is similar to the XRD spectra of paminobenzene sulfonic acid intercalated LDHs-MMT complex in the literature [44]. The obtained characteristic peaks of the intercalation complexes from the above XRD spectrum simulation may provide some theoretical references for the experimental testing of material structure.…”
Section: Electronic Structural Property Of His-ldhs-mmtsupporting
confidence: 83%
See 1 more Smart Citation
“…Other peak types are basically a combination of peak shapes of MMT and LDHs. It is similar to the XRD spectra of paminobenzene sulfonic acid intercalated LDHs-MMT complex in the literature [44]. The obtained characteristic peaks of the intercalation complexes from the above XRD spectrum simulation may provide some theoretical references for the experimental testing of material structure.…”
Section: Electronic Structural Property Of His-ldhs-mmtsupporting
confidence: 83%
“…Fraser et al [44] studied chiral differences in the effects of D-and L-histidine on the interlayer spacing of vermiculite clays. The results demonstrated that the effect of different enantiomers of an amino acid may alter physical and structural properties of clay systems at low amino acid concentrations and over a long length-range.…”
Section: Introductionmentioning
confidence: 99%
“…The template-catalyzed polymerization of clay formation could be a possible amplification mechanism for the enrichment of chiral molecules in carbonaceous chondrite meteorites. In recent studies, Fraser et al (2011aFraser et al ( , 2011b provided experimental evidence for the chiral enrichment of amino acids on vermiculite crystals. It is therefore important from the point of view of prebiotic chemistry whether organic acids like oxalic acid might have catalyzed the formation of the phyllosilicate phases on these meteorites.…”
Section: Introductionmentioning
confidence: 99%
“…The lysine data show a very small decrease in D/L that is just significant at the level of analytical precision. In addition to this significant difference in behaviour, and the implications of the DFT and MD simulations, neutron diffraction data showed no significant reverse shift in the dspacing on going from L-to D-enantiomer over the timescale of the whole experiment (~6 hours) 48 . All these data suggest that in the amino acid-clay system, there is a lack of short term reversibility and this lends support to the proposition that amino acids are bound directly and strongly to the clay surface.…”
Section: Discussionmentioning
confidence: 88%